2015
DOI: 10.1002/mana.201400343
|View full text |Cite
|
Sign up to set email alerts
|

Existence and general decay for nondissipative hyperbolic differential inclusions with acoustic/memory boundary conditions

Abstract: In this paper, we prove the existence and general energy decay rate of global solution to the mixed problem for nondissipative multi-valued hyperbolic differential inclusionswith memory boundary conditions on a portion of the boundary and acoustic boundary conditions on the rest of it. For the existence of solutions, we prove the global existence of weak solution by using Galerkin's method and compactness arguments. For the energy decay rates, we first consider the general nonlinear case of h satisfying a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…After [25] many authors showed decay results of the energy to problems involving memory and acoustic boundary conditions, see [3,4,[15][16][17][18]23,26]. We highlight the work of Boukhatem and Benabderrahmane [4] where was showed blow up of solutions.…”
Section: )mentioning
confidence: 76%
“…After [25] many authors showed decay results of the energy to problems involving memory and acoustic boundary conditions, see [3,4,[15][16][17][18]23,26]. We highlight the work of Boukhatem and Benabderrahmane [4] where was showed blow up of solutions.…”
Section: )mentioning
confidence: 76%
“…The asymptotic behavior was obtained in Beale 3 (Theorem 2.6). Recently, wave equations with acoustic boundary conditions have been studied by many authors 5–19 …”
Section: Introductionmentioning
confidence: 99%
“…For more papers on acoustic boundary conditions studying the interaction with memory or delay terms, we can refer to previous studies. [8][9][10] Generally, the case of variable coefficients (A(x) ≠ I) reflects the inhomogeneous nature of materials which has a wide application in natural sciences. Many researchers investigated wave equations with variable coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we know from Gal et al 7 that the dynamic boundary conditions has a connection with acoustic boundary conditions. For more papers on acoustic boundary conditions studying the interaction with memory or delay terms, we can refer to previous studies 8‐10 …”
Section: Introductionmentioning
confidence: 99%